The K-complex as a special reactive sleep slow wave – A theoretical update. (October 2016) - Halász, Péter
Summary: We aimed to integrate new data about K-complex (KC) physiology and relate KC to other low-frequency waves observed in slow wave sleep. KC can be considered a 'prototype' of reactive sleep slow waves. Similarly to slow waves, KCs feature up- and down-states, they are subject to homeostatic regulation but they are also associated with sensory activation. As a part of the continuum of reactive sleep slow waves, the study of the KC may offer a better understanding of how slow waves are activated by the sensory system. KCs appear to have a special place among sleep slow waves and in the newly established framework of input-related NREM sleep regulation. It is a key element highlighting how the brain may choose to maintain sleep in response to a sensory input when facing the question "to wake or not to wake".